SELF-PERCEPTION OF HEALTH AMONG VISITORS TO PUBLIC PARKS IN TERESINA (Fiep Bulletin - online, 2025)
Introduction: Public parks have emerged as spaces that contribute to promoting health and well-being among visitors, positively influencing their self-perceived health. Objective: To assess the prevalence and factors associated with self-perceived health among visitors to public parks in Teresina, PI. Methods: This is a descriptive, cross-sectional study conducted with a sample of 102 adult visitors from two public parks in Teresina, Piauí. The online questionnaire for data collection included a question about self-perceived health: "How do you rate your health?" along with sociodemographic, behavioral, and health characteristics. Statistical analysis included descriptive measures of absolute and relative frequency and Pearson's chi-square test, with p-values
Keywords: Green Spaces; Urban Parks; Health Promotion